Adaptation of Barley Powdery Mildew (Blumeria graminis f. sp. hordei) in Western Australia to Contemporary Agricultural Practices - Tucker, Madeline Ann (Curtin University, 2015)
History has shown that the repeated use of fungicides in agriculture can lead to resistance. In Australia, contemporary agricultural practices have utilised wide-scale barley monocultures often harbouring a single dominant gene for mildew resistance. High disease incidences have necessitated the application of fungicides – with each registered formulation containing a triazole. This study details the rapid adaptation of powdery mildew in WA. Where, with disappointing predictability, many resistance genes and fungicides no longer provide effective control.